Review of the Transition From Smouldering to Flaming Combustion in Wildfires - Santoso, Muhammad A.; Christensen, Eirik G.; Yang, Jiuling; Rein, Guillermo (Frontiers in Mechanical Engineering, 2019)
Wildfires are the occurrence of uncontrolled combustion in the natural environment (forest, grassland, or peatland). The frequency and size of these fires are expected to increase globally due to climate change, land use, and population movement, posing a significant threat to populations living at the wildland urban interface (WUI), as well as to habitats and the environment. Wildfires can be broadly divided into two types, smouldering (heterogeneous combustion) and flaming (homogeneous combustion). Both are important in wildfires and despite being characteristically different, one can lead to the other. The smouldering-to-flaming (STF) transition is considered threatening because it represents a sudden increase in spread rate, power, and hazard. STF transition is a sudden initiation of homogeneous gas-phase ignition preceded by smouldering combustion, and needs sufficient oxygen supply, thermal energy production, and pyrolysis products. Its unpredictable occurrence, temporally and spatially, poses an additional challenge in wildfire prevention and mitigation. For example, flaming fire may reignite through the STF transition of an undetected smouldering fire, or the transition from ember. The current understanding of the mechanisms leading to the transition is poor. Strong oxidation of char is a plausible mechanism due to its high exothermicity, acting both as heat source in driving gaseous fuel production and ignition source of the gaseous fuel. Broadly, the literature has identified two variables that govern the STF transition, i.e. oxygen supply and heat flux, on samples ranging from 0.1 to 1.22 m. Airflow velocity has competing effects. It increases oxygen supply to the reaction zone, thus increasing the reaction rate of oxygen-limited spread, but simultaneously increases convective cooling. Permeability of a fuels and fuel ability to remain consolidated (maintain its integrity) during burning influences the propagation of smouldering. Permeability controls the oxygen penetration into the fuel, and consolidation allows the formation of internal pores where STF can take place. Considering the high complexity of the STF transition problem, more studies are needed on different types of fuel, especially on wildland fuels. This review synthesizes the research and identifies regions for further research as well as informs on various STF transition mechanisms in the literature.